Modeling future climate change impacts on sorghum (Sorghum bicolor) production with best management options in Amhara Region, Ethiopia - Adem Mohammed; Abebe Misganaw (CABI Agriculture and Bioscience)
Abstract Sorghum is one of the most important cereal crops well adapted in arid and semi-arid areas of Ethiopia but yield is low as compared to its potential. The crop has been adversely affected by climate change and climate variability accompanied by low soil fertility, insects and weeds. Thus, assessment of impact of projected climate change is important for developing suitable management strategies. The present study was conducted with the objectives (1) to calibrate and evaluate the CERES-sorghum model in DSSAT (2) to assess impact of projected climate change on sorghum production in 2030s (2020–2049) and 2050s (2040–2069) under RCP4.5 and RCP8.5 scenarios and (3) to identify best crop management strategies that can sustain sorghum production. The CERES-sorghum model was calibrated and evaluated using field experimental data of anthesis, physiological maturity, grain yield and aboveground biomass yield. In the simulation, the initial weather and CO2 were modified by future climates under the two climatic change scenarios (RCP4.5 and RCP8.5). Historical daily weather data (1981–2010) of rainfall, maximum temperature, minimum temperature, and solar radiation were obtained from the nearest weather stations at Sirinka and Kombolcha while future climate date for 2030s and 2050s were downloaded from the ensemble of 17 CMIP5 GCM outputs run under RCP4.5 and RCP8.5 downscaled to the study sites using MarkSim. Different sowing dates, nitrogen rates, and supplemental irrigation were evaluated for their effectiveness to increase sorghum yield under the present and future climate conditions of the study area. The result of model calibration showed that the RMSE for anthesis, physiological maturity, grain yield, and above-ground biomass yield were 2 days, 2 days, 478 kg ha−1, and 912 kg ha−1, respectively with normalized nRMSE values of 2.74%, 1.6%, 13.42%, and 5.91%, respectively. During the model evaluation the R2 values were 78% for anthesis, 99% for physiological maturity, 98% for aboveground biomass yield, and 94% for grain yield. The d-statistics values were 0.87, 0.91, 0.67, and 0.98 while the nRMSE values were 2.6%, 2.7%, 23.4%, and 4.1% for the respective parameters. The result of statistical analysis for both model calibration and evaluation revealed that there existed strong fit between the simulated and observed values that indicated the model can be used for different application to improve sorghum productivity in the region. The result of impact analysis showed that sorghum grain yield may decrease by 2030s and 2050s under both RCPs scenarios. However, the result of management scenarios showed that sorghum yield may be substantially increased through use of optimum nitrogen fertilizer, application of supplemental irrigation and by using early sowing dates individually or in combination. In conclusion, projected climate change could adversely affect sorghum production in the semi-arid areas of Ethiopia in the present and future climate conditions but impact could be reduced by using suitable crop management strategies.